Edemogenic test and hydrogen peroxide degradation rate of bleaching gels with different desensitizing agents - Briso, André Luiz Fraga; Gallinari, Marjorie Oliveira; Benetti, Francine; Valentim, Diego; Bueno, Carlos Roberto Emerenciano; Marson, Fabiano Carlos; Junior, Eloi Dezan; Cintra, Luciano Tavares Ângelo (Brazilian Dental Science, 2018)
Objective: The at-home bleaching technique leads to the intimate contact of the bleaching gel with gingival tissues, so this study evaluated the immediate inflammatory response, through the edemogenic test, induced by at-home bleaching gels of 10% carbamide peroxide with different desensitizing agents, the quantification of hydrogen peroxide released and bleaching gels pH. Material and Methods: Forty-eight rats were divided into groups (n=12): CTRL-control group, WP-Whiteness Perfect 10% (FGM Produtos Odontológicos, Joinville, SC, Brazil), OPA-Opalescence 10% (Ultradent Products Inc., South Jordan, IT, USA), and PB-Power Bleaching (BM4, Palhoça, SC, Brazil). For the edemogenic test, all rats received an intravenous injection of Evan's Blue; after 30 min, 0.2 mL of each bleaching gels was injected into the subcutaneous tissue of the rats, and the results of the vascular permeability were assessed after 3 and 6h. The amount of HP released and pH of each product was also determined. Data were submitted to statistical test (p